2022
DOI: 10.1093/bib/bbac067
|View full text |Cite
|
Sign up to set email alerts
|

A review of SNP heritability estimation methods

Abstract: Over the past decade, statistical methods have been developed to estimate single nucleotide polymorphism (SNP) heritability, which measures the proportion of phenotypic variance explained by all measured SNPs in the data. Estimates of SNP heritability measure the degree to which the available genetic variants influence phenotypes and improve our understanding of the genetic architecture of complex phenotypes. In this article, we review the recently developed and commonly used SNP heritability estimation method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…SNPs are among the high‐risk alterations associated with cancer occurrence. 295 85% of SNP are annotated in noncoding regions and related to disease development. These abnormalities could influence the expression and function of lncRNA downstream targets.…”
Section: Lncrnas and Circrnas In Neuroblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…SNPs are among the high‐risk alterations associated with cancer occurrence. 295 85% of SNP are annotated in noncoding regions and related to disease development. These abnormalities could influence the expression and function of lncRNA downstream targets.…”
Section: Lncrnas and Circrnas In Neuroblastomamentioning
confidence: 99%
“…SNPs are among the high‐risk alterations associated with cancer occurrence 295 . 85% of SNP are annotated in noncoding regions and related to disease development.…”
Section: Lncrnas and Circrnas In Neuroblastomamentioning
confidence: 99%
“…For comparison, we also conducted the univariate GWAS of each of the amygdala nuclei. The SNP-based heritability, representing the phenotypic variance that arises due to the genetics, was also estimated [16]. Second, we discovered gene-level and gene-set associations, explored the functional mechanisms of the significant SNPs, and performed association lookups within the NHGRI-EBI GWAS catalog [17].…”
Section: Introductionmentioning
confidence: 99%
“…SNP mainly refers to DNA sequence polymorphism at the genome level, which is the most ideal marker for DNA inheritance and molecular breeding ( Kruglyak, 1997 ). It can be used to establish a variety of analytic models to estimate the degree of heritable variation and phenotypes, thus, it can be used as the biomarker for biological breeding process ( Tang et al, 2022 ). Yao et al (2022) have found the key SNPs in genes of melatonin synthesis in Holstein dairy cows.…”
Section: Introductionmentioning
confidence: 99%